Physiotherapeutic management in the separation of the white borderline - Kubiak, K.; Kwiatkowska, K.; Lamtych, M.; Zukow, W.; Strojek, K. (Pedagogy and Psychology of Sport, 2019)
Dissolution of the white border of the rectus abdominal muscle is a disruption of the functioning of the rectus muscle, which results in loosening of the white border. As a result, a characteristic muscle stretch is visible. This defect affects a significant number of pregnant women and is not just an aesthetic problem. There are many factors that contribute to the above-mentioned ailments. To get the best treatment results, it is important to diagnose the problem early. For this purpose, special tests are used. The ease with which they are made enables the patient to control the separation of the frontier by the patient. The implementation of therapy should take place already in the first days after delivery. It is important to start therapy with posture corrective exercises, breathing exercises and learning how to properly perform everyday activities. Then we implement exercises that involve the abdominal muscles. The exercise program can be supplemented with dynamic slicing. A holistic approach to the problem and combining different forms of therapy allows you to obtain optimal results.